Our Australian girl - Hamer, Michelle (Puffin, 2014)
It's 1930 and Daisy's worst nightmare has come true. She's alone on the streets, separated from her family. Things get worse after the police send her to live at the Melbourne orphanage. At least she doesn't have to scavange for food scraps anymore, but with no family, Daisy is miserable. When she hears some shocking news she decides it's time to plot a daring escape..
Keywords: Geschichte 1900-2000; Moving, Household / Juvenile fiction; Country life / Australia / Juvenile fiction; Moving, Household / Australia / Juvenile fiction; Children's stories; Country life; Manners and customs; Moving, Household; Alltag, Brauchtum; Melbourne (Vic.) / Social life and customs / 20th century / Juvenile fiction; Australia / Social life and customs / 1929-1939 / Juvenile fiction; Australia; Victoria / Melbourne; Australien